Comparison of QT/RR Relationship Using Two Algorithms of QT Interval Analysis for Identification of High Risk Patients for Life-Threatening Ventricular Arrhythmias - Kiuge, Petra; Walter, Thomas; Neugebauer, Annerose (Annals of noninvasive electrocardiology, 1997)
Objective: The purpose of this study was to evaluate the dynamic relationship between QT and RR intervals considering either the QTe interval (i.e., time between the onset of QRS and the end of the T wave) or the QTa interval (i.e., time between the onset of QRS and the apex of the T wave) from 30‐second modules. Method: The Holter recordings in three groups of adult subjects (30 patients with malignant ventricular tachyarrhythmias [VT/VF patients], 40 patients with coronary artery disease [CAD], and 44 normal subjects) were analyzed using the ELATEC System. Results: In normal subjects the correlation coefficient between QTa and RR (QTa/RR) was significantly higher (0.87 ± 0.12) than those between QTe and RR (QTe/RR) (0.79 ± 0.17). In the other groups there was no significant difference between QTa/RR and QTe/RR: QTa/RR (CAD: 0.71 ± 0.3; VT/VF: 0.73 ± 0.19); and QTe/RR (CAD: 0.63 ± 0.33; VT/VF: 0.69 ± 0.21). The slope of QTe/ RR over 24 hours was significantly larger in VT/VF patients (0.23 ± 0.11) than in the other groups (control: 0.18 ± 0.08; CAD: 0.17 ± 0.1). Measuring the QTa/RR relation there was no difference between the three groups (VT/VF: 0.19 ± 0.09; CAD: 0.15 ± 0.09; normal: 0.19 ± 0.06). Conclusion: QTe/RR as well as QTa/RR analyses are methods of detecting a deranged rate dependence of QT intervals in high risk patients. An increased QTe/RR slope indicates a higher risk of life‐threatening ventricular arrhythmias. Because there was no difference in QTa/RR we conclude that the end of the T wave gives important information about disorders in repolarization.